A Review of the Advances and Challenges in Measuring the Thermal Conductivity of Nanofluids - Reinaldo R. Souza; Vera Faustino; Inês M. Gonçalves; Ana S. Moita; Manuel Bañobre-López; Rui Lima (Nanomaterials, 2022)
Fluids containing colloidal suspensions of nanometer-sized particles (nanofluids) have been extensively investigated in recent decades with promising results. Driven by the increase in the thermal conductivity of these new thermofluids, this topic has been growing in order to improve the thermal capacity of a series of applications in the thermal area. However, when it comes to measure nanofluids (NFs) thermal conductivity, experimental results need to be carefully analyzed. Hence, in this review work, the main traditional and new techniques used to measure thermal conductivity of the NFs are presented and analyzed. Moreover, the fundamental parameters that affect the measurements of the NFs’ thermal conductivity, such as, temperature, concentration, preparation of NFs, characteristics and thermophysical properties of nanoparticles, are also discussed. In this review, the experimental methods are compared with the theoretical methods and, also, a comparison between experimental methods are made. Finally, it is expected that this review will provide a guidance to researchers interested in implementing and developing the most appropriate experimental protocol, with the aim of increasing the level of reliability of the equipment used to measure the NFs thermal conductivity.